Analysis for Flow of an Incompressible Brinkman-Type Fluid in Thin Medium with Friction. (22nd September 2021) - Manaa, Soumia; Boulaaras, Salah; Benseridi, Hamid; Dilmi, Mourad; Alodhaibi, Sultan
Abstract : In this paper, we consider the Brinkman equation in the three-dimensional thin domain ℚ ε ⊂ ℝ 3 . The purpose of this paper is to evaluate the asymptotic convergence of a fluid flow in a stationary regime. Firstly, we expose the variational formulation of the posed problem. Then, we presented the problem in transpose form and prove different inequalities for the solution u ε, p ε independently of the parameter ε . Finally, these estimates allow us to have the limit problem and the Reynolds equation and establish the uniqueness of the solution.